The equilibrium theory of inhomogeneous polymers - Fredrickson, Glenn Harold; Oxford eBooks (Oxford : Clarendon, 2006)
This work provides a pedagogical introduction to the theoretical and computer simulation techniques that are useful in the design of polymer formulations including personal care products multiphase plastic materials and processed foods.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Polymers -- Mathematical models; Inhomogeneous materials; Polymer solutions; Electronic books